PERMASALAHAN POLA ASUH DALAM MENDIDIK ANAK DI ERA DIGITAL - Waruwu, Pascalia Rumine (DUNIA ANAK: Jurnal Pendidikan Anak Usia Dini, 2020)
Parents are currently faced with various problems that occur in educating children amidst rapid digital development. This raises various concerns about children's growth and development. This article aims to examine the problems that occur in the process of educating children in today's digital era. All problems in educating children should be addressed with the right pattern and approach. This research uses a research synthesis approach in exploring relevant theories related to the issues discussed. Qualitative analysis is the spearhead of research to strengthen the accuracy of the data collected. In this era, many children have a behavior that is dependent on digital devices which is quite serious and has a negative side. Therefore, the importance of controlling the digital era held by children to focus on the field of education needs to be done so that motivation can be formed and educational goals can also be achieved well with synergy between educational institution (school) stakeholders and others (educational trilogy).